GIS-based disaster management system in local Government of West Aceh, Sumatera, Indonesia: Technology Acceptance Factors Affecting Intention To Adopt Geographical Information System (GIS) Among The Local Governments In West Aceh, Sumatera, Indonesia. - Mirda, Jamal (2010)
Tersedianya data/maklumat yang tepat adalah bahagian yang penting untuk mengatasi persoalan-persoalan saat menangani pelbagai bencana.